Beware of Sensing Culture in the Metaverse Era - Widia Sri Ardias; Amrizal, Amrizal; Riyono, Bagus (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
The metaverse is a 3-dimensional (3D) digital ecosystem that allows individuals to conduct communication and social interactions, financial transactions, and various other interactions using digital technology. Entering this metaverse era, many new behaviors are formed and old cultures are abandoned. This change in the way humans live to fulfill their various needs has made the dynamics of social life change from direct real interaction to digital. This of course provides convenience as well as challenges in human civilization. This research discusses the challenges and opportunities of the metaverse for Indonesian society. The research method used is a literature study by collecting library data, reading and recording, and managing research materials with the literature design used is a narrative review. The results showed that the emergence of the metaverse in the last two decades has changed human behavior, including the rise of online learning in the education sector, the disappearance of various types of manual work and replaced with new digital-based jobs, massive digital-based financial transaction activities. The toughest challenge in this era is the decline in human critical thinking power, the collapse of moral nobility and the shift in social ethics in community life. The metaverse era is an inevitable condition, and requires careful preparation by society to deal with it. In addition to the demands of the stockholder’s ability to provide the necessary equipment, human resources must also be equipped with qualified abilities to control various sophisticated equipment in this era. On the other hand, the strengthening of noble values both from Religion, Culture, and Nationality should be strengthened so that humans are not trapped in a culture of sensation known as sensing culture.